Reductive amination of ω-conotoxin MVIIA: synthesis, determination of modification sites, and self-assembly - Xiufang Ding; Yue Wang; Sida Zhang; Ruihua Zhang; Dong Chen; Changcai Liu; Jianfu Xu; Long Chen (Amino Acids, 2024)
Abstract Peptide drugs have disadvantages such as low stability, short half-life and side effects, which limit their widespread use in clinical practice. Therefore, peptide drugs can be modified to improve these disadvantages. Numerous studies have shown that alkyl-modified peptide drugs can self-assemble to prolong the duration of efficacy and/or reduce side effects. However, the commonly used solid-phase synthesis method for alkyl-modified peptides is time-consuming. To overcome this, a simple reductive amination reaction was employed, which can directly graft the alkyl chain to the peptide sequence and effectively avoid stepwise synthesis from C- to N-terminal with amino acids. In this study, ω-conotoxin MVIIA was used as the peptide drug, while myristic aldehyde was used as the alkylating agent. To obtain the maximum productivity of modified peptides, the molar ratio of peptide MVIIA to myristic aldehyde in the reductive amination reaction was optimized. Furthermore, the peptide modification sites in this reaction were confirmed by secondary mass spectrometry analysis. Besides, alkyl-modified peptide MVIIA was able to form micelles by self-assembly and improved stability in serum, which was related to our previous work where myristoylated peptide MVIIA micelles can improve the drug stability. Finally, this study was intended to provide a methodological basis for modifying the alkyl chain of peptide drugs.